2009
DOI: 10.1080/12538078.2009.10516160
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity ofThymus pallidusBatt. and determination of the chemical composition of its essential oil

Abstract: Antibacterial activity of Thymus pallidus Batt. and determination of the chemical composition of its essential oil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…The oil of T. satureioides, which is an endemic species of Morocco, was reported to contain borneol (29.4%), camphene (11.8%) and α-pinene (6.6%) [7]. Another study showed that the essential oil of T. pallidus, which is also an endemic species of Morocco, contained α-terpinene (42.2%), thymol (23.9%) and β-ocimene (8.3%) [12]. Generally, a great variability and diversity is observed concerning the chemical composition of the essential oils of Thymus species and subspecies of different origin due to climatic and soil variations, to the vegetative cycle, and to seasonal variation [13,14].…”
mentioning
confidence: 99%
“…The oil of T. satureioides, which is an endemic species of Morocco, was reported to contain borneol (29.4%), camphene (11.8%) and α-pinene (6.6%) [7]. Another study showed that the essential oil of T. pallidus, which is also an endemic species of Morocco, contained α-terpinene (42.2%), thymol (23.9%) and β-ocimene (8.3%) [12]. Generally, a great variability and diversity is observed concerning the chemical composition of the essential oils of Thymus species and subspecies of different origin due to climatic and soil variations, to the vegetative cycle, and to seasonal variation [13,14].…”
mentioning
confidence: 99%
“…Quand à la concentration minimale bactéricide la plus faible égalant à 0.031% est enregistrée pour les HEs des plantes Mentha pulegium et Thymus satureioides (Chraibi et al, 2016), suivie par celle de l'HE de Thymus pallidus Batt étant de 0.08% (Sqalli et al, 2009), alors que la CMB d'HE de Mentha piperita vient au dernier rang avec une valeur de 0.5% contre M. smegmatis (Chraibi et al, 2017 Précédemment, il est rapporté par plusieurs recherches que ces molécules sont dotées d'un effet antimycobactérien (Haouat et al, 2013 ). Prenant par exemple, le cas de l'étude réalisée par Anand et ses collaborateurs (2006) ayant montré que l'épigallocatechin-3-gallate, un composant majeur des polyphénols du thé vert, inhibe la croissance de M. tuberculosis survivant à l'intérieur des macrophages humains via la régulation négative de l'expression d'un gène codant pour la coronine-1, appelée encore TACO (pour tryptophan aspartate containing coat protein) à travers l'inhibition de l'activité de facteur de transcription Sp1.…”
Section: Discussionunclassified
“…Therefore, the most encountered compounds are α-Terpinene, thymol, carvacrol, β-ocimene, menthone, borneol, ρ-cymene, β-linalol and caryophyllene. These bioactive molecules are responsible for its antioxidant, antifungal, antibacterial and anti-tumor properties (Fadli et al 2011;Jaafari et al 2007;Jamali et al 2012;Sqalli et al 2009).…”
Section: Introductionmentioning
confidence: 99%